The Issue of Equity Taking Research on Partnership Program Development to Scale in Practice - Epstein, Joyce (International Journal about Parents in Education, 2023)
Looking to the future, a very challenging topic in the U. S. and in other nations is the “scaleability” of research-based (or evidence-based) results of partnership programs and practices. After more than three decades of studies by countless researchers that confirm the importance of school, family, and community partnerships for student success in school, it is imperative to translate research to good policy and useful practice so that more schools—indeed all schools— organize effective programs to engage parents, other family members, and community partners in ways that support student success in school. There are opportunities in each nation to attain this imperative and there are challenges that limit progress. What have we learned about both opportunities and challenges to press forward so that schools develop and sustain goal-linked partnership programs to increase student achievement, good behavior, postsecondary planning, and other indicators of success? This question is at the heart of the equity issues discussed at ERNAPE-Lisboa.